Spatially resolved diffusion pore imaging using k-space readout - Oswald, Lucas; Rauch, Julian; Laun, Frederik B.; Ladd, Mark E.; Kuder, Tristan Anselm (Magnetic resonance imaging, 2025)
Nuclear magnetic resonance diffusion methods are powerful tools for investigating the underlying structure of materials or tissues. Diffusion pore imaging (DPI) provides access to information about the geometric shape of pores containing diffusible substances. This technique yields an averaged image of the pores present in the imaging volume and enables measurements at a scale much smaller than that of conventional MR imaging. For applications in non-homogeneous materials such as biological tissues or heterogeneous porous media, the integration of a second spatial encoding step is essential to distinguish pore shapes in different regions of the measurement volume. Here, we present a combination of two-dimensional q-space and two-dimensional k-space acquisition on a Bruker 9.4 T small animal scanner. A 2D pore space function is reconstructed in each image voxel obtained from k-space. The long-narrow sequence scheme necessary for DPI was extended with a conventional k-space imaging readout to fill both k- and q-space. A conventional spin-echo approach with a single refocusing pulse was employed. From two different regions of interest, the sizes of capillaries with inner diameters of 15 μm and 20 μm, respectively, present in a phantom could be estimated from one- and two-dimensional projections of the pore space function. Simulations using the multiple correlation function approach exhibit good agreement with the measured one-dimensional pore space functions. Existing residual phases in the measurement data were corrected using phase reference measurements in a structureless oil phantom. In summary, spatially resolved pore imaging allows for the reconstruction of pore shapes in specific regions of interest, reinforcing the potential of DPI to non-invasively explore cellular structure. This study demonstrates the ability to reveal the voxel-averaged shape of pore distributions within a single DPI measurement on a preclinical MR scanner.
Online verfügbar: 7. Juli 2025, Artikelversion: 16. Juli 2025
Gesehen am 18.11.2025